2002
DOI: 10.1111/j.1469-8749.2002.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Wartenberg pendulum test: objective quantification of muscle tone in children with spastic diplegia undergoing selective dorsal rhizotomy

Abstract: The aim of this study was to investigate the reliability and sensitivity of the Wartenberg pendulum test for quantification of muscle tone in young children with spastic diplegia undergoing selective dorsal rhizotomy (SDR). Fourteen non‐disabled children (mean age of 5.5 years, age range 2.3 to 8.8 years, one female and one male in each year) were tested twice. Twenty children with spastic diplegia (12 males, eight females; mean age of 4.3 years, age range 2.5 to 6.3 years) consecutively selected for SDR, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…In a testretest (7-14 days apart) reliability of the pendulum test performed on able-bodied children 3-8 years old reported coefficient of variance ranging from 3 to 47% for variables calculated from the pendulum test [3]. An inter-day reliability study on able-bodied adults revealed a large range in reliability with ICC ranging from 0.08 to 0.88 on 10 variables recorded using an electrogoniometer [12].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a testretest (7-14 days apart) reliability of the pendulum test performed on able-bodied children 3-8 years old reported coefficient of variance ranging from 3 to 47% for variables calculated from the pendulum test [3]. An inter-day reliability study on able-bodied adults revealed a large range in reliability with ICC ranging from 0.08 to 0.88 on 10 variables recorded using an electrogoniometer [12].…”
Section: Introductionmentioning
confidence: 95%
“…Increased tone/ spasticity of the rectus femoris, hamstrings and gastrocsoleus muscle groups are often associated with causing impaired walking and transfer abilities for children diagnosed with CP [1][2][3]. Numerous potential interventions can be used to treat spasticity in children with CP.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations